MRI-measured regression of carotid atherosclerosis induced by statins with and without niacin in a randomised controlled trial: the NIA plaque study. Issue 22 (19th July 2013) - Sibley, Christopher T; Vavere, Andrea L; Gottlieb, Ilan; Cox, Christopher; Matheson, Matthew; Spooner, Amy; Godoy, Gustavo; Fernandes, Veronica; Wasserman, Bruce A; Bluemke, David A; Lima, Joao A C
Abstract : Objective: To evaluate the benefit of niacin in addition to statin therapy on plaque regression among older individuals with established atherosclerosis. Design: Randomised, controlled, double-blind clinical trial. Setting: University outpatient center. Patients: 145 patients older than 65 years, half of them older than 75 years of age, with established atherosclerosis were enrolled. Interventions: Participants received either extended release niacin (1500 mg daily) or placebo in addition to statin therapy to reach their National Cholesterol Education Program-defined low density lipoprotein (LDL) cholesterol target. Main Outcome Measures: The primary endpoint was reduction in the wall volume of the internal carotid artery (ICA) measured by MRI. Results: After 18 months, high density lipoprotein cholesterol was higher with statins plus niacin compared with statins alone (1.6±0.4 vs 1.4±0.4 mmol/L p<0.001). Both groups had significant decreases in the main outcome measure of ICA wall volume, which regressed at 0.5%/month (SEM 0.2, p=0.004) in the statins plus placebo group and at 0.7%/month in the statins plus niacin group (SEM 0.2, p<0.001). There was no difference in the rate of regression between groups (p=0.49). Conclusions: Treatment with statin therapy to presently recommended LDL levels, with or without niacin, resulted in significant atherosclerosis reduction.